HOW TO ENHANCE MOTIVATION AND BIOLOGY LEARNING OUTCOMES? - Dharmadewi, A.A. Istri Mirah; I Gusti Ayu Rai; Jayantika, I Gusti Agung Ngurah Trisna (Indonesian Journal of Educational Development (IJED), 2024)
The study aims to determine the effect of inquiry-based learning strategies assisted by presentations and tiered questions on the motivation and biology learning outcomes of 10th-grade students at SMA Negeri 2 Denpasar. This type of research is classified as quasi-experimental with an Non-Equivalent Post-Test-Only Control Group Design. The sample in this study consists of students from class X IPA 7 and class X IPA 5 at SMA N 2 Denpasar, involving a total of 2 classes selected using the random sampling technique. The data obtained is quantitative data in the form of learning motivation scores and biology learning outcomes. Analysis using MANOVA with the help of SPSS 23.0 for Windows. The results of the hypothesis test show the following results: there is an influence of the inquiry learning strategy assisted by presentations and tiered questions on motivation, there is an influence of the inquiry learning strategy assisted by presentations and tiered questions on learning outcomes, there is a simultaneous influence of the inquiry learning strategy assisted by presentations and tiered questions on motivation and biology learning outcomes in the X IPA class at SMA Negeri 2 Denpasar.